(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Institute of Chartered Accountants of India (ICAI) has announced its decision to adopt IFRS in India with effect from 1 April, 2011. The standards will have a significant impact on capital markets. Many European countries shifted to IFRS as early as 2005. An understanding of Indian Generally Accepted Accounting Principles (GAAP) and IFRS standards is an urgent need of hour. Therefore, by investigating the perception of IFRS, this study aims to assess the level of planning for adopting the standards in India. International Financial Reporting Standards (IFRS) is a set of accounting standards developed by an independent, not-for-profit organization called the International Accounting Standards Board (IASB).The goal of IFRS is to provide a global framework for how public companies prepare and disclose their financial statements. IFRS provides general guidance for the preparation of financial statements, rather than setting rules for industry-specific reporting. Having an international standard is especially important for large companies that have subsidiaries in different countries. Adopting a single set of world-wide standards will simplify accounting procedures by allowing a company to use one reporting language throughout. A single standard will also provide investors and auditors with a cohesive view of finances. The present paper focuses on understanding the background of IFRS, and its objectives. The process involved in adoption of International Financial Reporting Standards in India is discussed in detail along with the benefits of standards to various parties involved, in general and in specific. The researcher has analyzed the challenges faced in implementations of IFRS in India and utilities of post IFRS regime in India.